Limestone and silica powder replacements for cement: Early-age performance. (April 2017) - Bentz, Dale P.; Ferraris, Chiara F.; Jones, Scott Z.; Lootens, Didier; Zunino, Franco
Abstract: Developing functional concrete mixtures with less ordinary portland cement (OPC) has been one of the key objectives of the 21st century sustainability movement. While the supplies of many alternatives to OPC (such as fly ash or slag) may be limited, those of limestone and silica powders produced by crushing rocks seem virtually endless. The present study examines the chemical and physical influences of these powders on the rheology, hydration, and setting of cement-based materials via experiments and three-dimensional microstructural modeling. It is shown that both limestone and silica particle surfaces are active templates (sites) for the nucleation and growth of cement hydration products, while the limestone itself is also somewhat soluble, leading to the formation of carboaluminate hydration products. Because the filler particles are incorporated as active members of the percolated backbone that constitutes initial setting of a cement-based system, replacements of up to 50% of the OPC by either of these powders on a volumetric basis have minimal impact on the initial setting time, and even a paste with only 5% OPC and 95% limestone powder by volume achieves initial set within 24 h. While their influence on setting is similar, the limestone and silica powders produce pastes with quite different rheological properties, when substituted at the same volume level. When proceeding from setting to later age strength development, one must also consider the dilution of the system due to cement removal, along with the solubility/reactivity of the filler. However, for applications where controlled (prompt) setting is more critical than developing high strengths, such as mortar tile adhesives, grouts, and renderings, significant levels of these powder replacements for cement can serve as sustainable, functional alternatives to the oft-employed 100% OPC products.